1985
DOI: 10.1002/tera.1420310115
|View full text |Cite
|
Sign up to set email alerts
|

Maternal toxicity: A possible etiological factor in embryo‐fetal deaths and fetal malformations of rodent‐rabbit species

Abstract: Data from animal teratology studies were surveyed to determine whether embryo-fetal mortality and fetal malformations result from a primary action of the agent on the conceptus or if they are secondary to maternal toxicity--a consequence of administration with high dose levels of test chemicals. A fairly strong association between embryo-fetal mortality and maternal toxicity was revealed by analysis of data from hamsters, mice, rats, and rabbits in 234 studies of chemical and physical agents, of which 83 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
3

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(72 citation statements)
references
References 248 publications
3
65
1
3
Order By: Relevance
“…**p<0.01 in relation to other groups. Khera (1985) correlated the low frequency of fetal malformations to the maternal weight reduction and later defined maternal toxicity as transient, or permanent alterations in the maternal physiology with potential to cause adverse effects in the offspring during the embryo-fetal and post-natal development (Khera, 1987). Maternal toxicity can be observed through different approaches such as the clinical observation of body weight loss, locomotor alteration, diarrhea, piloerection, food intake reduction and maternal deaths (Khera, 1984;.…”
Section: Resultsmentioning
confidence: 99%
“…**p<0.01 in relation to other groups. Khera (1985) correlated the low frequency of fetal malformations to the maternal weight reduction and later defined maternal toxicity as transient, or permanent alterations in the maternal physiology with potential to cause adverse effects in the offspring during the embryo-fetal and post-natal development (Khera, 1987). Maternal toxicity can be observed through different approaches such as the clinical observation of body weight loss, locomotor alteration, diarrhea, piloerection, food intake reduction and maternal deaths (Khera, 1984;.…”
Section: Resultsmentioning
confidence: 99%
“…These data seem to suggest a correlation between the severity of maternal toxicity and the effects on the conceptuses, however a definite relationship cannot be extrapolated because the concurrent role of the test compound in inducing the effects must be taken into account. The role of maternal toxicity in the induction of adverse effects on conceptuses is a very long standing problem that has been faced by a number of researchers (Chahoud et al, 1999;Chernoff et al, 1989;ECETOC, 2004;Kavlock et al, 1985;Khera, 1984Khera, , 1985Paumgartten, 2010;Rogers et al, 2005), apparently without a definite solution. First of all the definition of maternal toxicity is very poor.…”
Section: Introductionmentioning
confidence: 99%
“…anomaly, misalignment, was evident in rat fetuses of the high dose group, but the increased incidence of this aberration was not significant on a litter basis. Khera (1985) has reviewed a number of teratology studies to examine the contributory role of maternal toxicity in the induction of fetal deaths and malformations. He concluded that certain malformations, including sternebra!…”
Section: Discussionmentioning
confidence: 99%